Willingness and professional motivations of medical students to work in rural areas: a study in Alexandria, Egypt - Aida M. Mohamed (PAGEPress Publications, 2013)
Retaining health workers in rural areas is challenging for a number of reasons, e.g. personal preferences, difficult work conditions and low remuneration. Our aim was to determine the effect of motivational factors on willingness to accept postings to rural underserved areas in Alexandria, Egypt and to identify perceived attributes of rural service.,A cross-sectional survey involving 302 4th-year medical students was conducted in March-July 2012. Logistic regression analysis was used to assess the association between students’ willingness to accept rural postings and their professional motivations, rural exposure and family parental professional and educational status (PPES). Perceived attributes to rural service were also assessed. Over 85% students were born in urban areas and 41.4% came from affluent backgrounds. More than half students reported strong intrinsic motivation to study medicine. After controlling for demographic characteristics and rural exposure, motivational factors significantly influenced willingness to practice in rural areas. High-family PPES was consistently associated with lower willingness to work in rural areas. A sizable portion of medical students are motivated to study and practice medicine in rural areas. Efforts should be made to build on motivation during medical training and designing rural postings, as well as favor lower PPES students for admission and improving organizational and contextual issues of rural service.